Behavior Analysis in Organizations: Quantitative data of Brazilian production - Nascimento, Erasmo Henrique de Araújo; Henklain, Marcelo Henrique Oliveira (Perspectivas em Análise do Comportamento, 2020)
There are several studies on Behavior Analysis in Organizations developed in Brazil, but this subarea of Behavior Analysis still lacks further dissemination and expansion of production. Therefore, the objective of this study was to carry out a literature review of the Brazilian behavioral-analytic production in organizations from 1970 to 2017. The following sources of information were consulted: (a) dissertations and theses: postgraduate programs sites with guidelines and / or lines of research in Behavior Analysis and the Brazilian Digital Library of Theses and Dissertations; (b) articles: CAPES Portal of Periodicals; (c) at the end of the consultations, the database was complemented with works from the OBM Library. The descriptors used and the procedures for research selection varied depending on the database adopted. The results suggest that the national production has grown in the last decade, although it is concentrated in the south and southeast of the country. It was also verified, considering an analysis of the most frequent words, compatibility between the studies found and concepts that characterize the behavioral-analytic theory and professional acting. Future research is suggested to extend the present exam including book chapters and studies presented at events.